Is physical activity related to renal cell carcinoma? A systematic review - Nader Mahdavi; Parisa Hosseinpour; Golnaz Dashti; Behnaz Bouzari; Rohollah Valizadeh; Babak Hassanlouei (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: Relationship between renal cell carcinoma and physical activity is not clear. Objectives: This study aimed to review the relationship between renal cell carcinoma and physical activity. Methods: We searched valid databases such as PubMed/Medline, Web of Science and Scopus for search of English papers by 30/12/2018. Eleven articles were selected for final assessment. We used Kidney cancer, Exercise, Kidney Neoplasm, Renal cancer, Physical activity, Renal cell carcinoma, Physical inactivity and Sedentary Lifestyle or a combination of them in the title/abstracts as the keywords. Results: There were 37,742 subjects reviewed in this systematic review of eleven published papers including five standard case-control, three cohorts and three population-based case-control design. Conclusion: According to the results, physical activity has a reverse relationship with renal cell carcinoma.